2016
DOI: 10.1210/jc.2015-2590
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Body Weight and Gestational Diabetes Differentially Influence Placental and Pregnancy Outcomes

Abstract: Context:Maternal obesity and gestational diabetes mellitus (GDM) can both contribute to adverse neonatal outcomes. The extent to which this may be mediated by differences in placental metabolism and nutrient transport remains to be determined.Objective:Our objective was to examine whether raised maternal body mass index (BMI) and/or GDM contributed to a resetting of the expression of genes within the placenta that are involved in energy sensing, oxidative stress, inflammation, and metabolic pathways.Methods:Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
84
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(94 citation statements)
references
References 81 publications
5
84
4
1
Order By: Relevance
“…Our finding of reduced AMPK in placental tissue of GDM offspring extends and supports the work of Martino et al [47] who reported reduced AMPK (PRKAA1) mRNA in placentae of gestational diabetic pregnancies. Muralimanoharan et al [48] reported a reduction in phosphorylated AMPK in placentae of women with GDM, but no change in total AMPK protein.…”
Section: Discussionsupporting
confidence: 92%
“…Our finding of reduced AMPK in placental tissue of GDM offspring extends and supports the work of Martino et al [47] who reported reduced AMPK (PRKAA1) mRNA in placentae of gestational diabetic pregnancies. Muralimanoharan et al [48] reported a reduction in phosphorylated AMPK in placentae of women with GDM, but no change in total AMPK protein.…”
Section: Discussionsupporting
confidence: 92%
“…It is consistent with previous reports where the TBARS levels were similar between the GDM and NPW placentas [19], and protein carbonyl formation was lower in the placentas of overweight patients compared to lean individuals [20], and more importantly, catalase and glutathione reductase (GSR) mRNA expression was higher in women with GDM compared with NPW [7]. Moreover, the TBARS and SOD concentrations were similar between the placentas from GDM and NPW [21].…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, increased nitration levels of MAPK and consequently reduced catalytic activity [23], suggesting a reduction of both the GLUT4 protein expression and mitochondrial biogenesis. Others found reduced gene expression for AMPK and mTOR in GDM placentas, but these authors did not determine protein expression [19]. Therefore, in the present study mitochondria content was indirectly determined by measuring the COX4 expression and ATPase activity.…”
Section: Discussionmentioning
confidence: 82%
“…Thus, it is unclear if there is truly an unexpected normalization in neonates of obese class I compared to overweight mothers. One mechanism to explain this finding would be the concept of protective adaptation 19 which is overwhelmed in extreme obesity. We also evaluated the possibility of clinical sequelae affecting our results.…”
Section: Discussionmentioning
confidence: 99%
“…18 Given the morbidities associated with excessive maternal weight and our understanding of the relationship between adiposity and inflammation, it has been postulated that maternal obesity causes increased intrauterine inflammation in both fetal and placental circuits. 19-21 However, there are limited data available on the effect of maternal obesity on neonatal inflammatory markers and immunoglobulin (Ig) levels such that specific aspects of this pathophysiology remain uncertain. 10, 20-24 …”
Section: Introductionmentioning
confidence: 99%